Traversing the Digital Era: The Amazing Evolution of Pen and Paper to Screens and Keyboards - Eslit, Edgar R. (Universitas Teuku Umar, 2023)
In this research article, the researcher delves into the ebb and flow of human ingenuity as the paper traces the evolution of writing from papyrus to pixels. Discover how humble instruments like quill pens and typewriters have propelled human into the digital frontier, forever reshaping the art of expression in the modern age. This article examines the evolution of writing tools from traditional pen and paper to digital writing in the modern age. It explores the development of writing materials such as papyrus, parchment, and paper, as well as the invention of writing tools including quill pens, fountain pens, and typewriters. The rise of digital writing tools, including word processing software and smartphones, is also discussed, along with their benefits such as increased efficiency and productivity, enhanced collaboration and sharing capabilities, and greater accessibility and flexibility. However, the article also highlights the challenges of writing in the digital age, including the impact of digital distractions on writing focus and quality, the issue of online plagiarism and copyright infringement, and the potential loss of traditional writing skills. The article concludes with recommendations for educators, school administrators, students, and researchers to strike a balance between digital and traditional writing practices, to embrace digital writing tools while preserving traditional writing skills, and to understand the importance of the evolution of writing. The theoretical frameworks of Social Construction of Technology (SCOT) Theory, Media Ecology Theory, and Activity Theory are also discussed in relation to the evolution of writing tools. Overall, this article provides valuable insights into the history, benefits, and challenges of writing in the digital age, as well as suggestions for navigating the future of writing and its tools.